2015
DOI: 10.1016/j.neuropsychologia.2015.10.033
|View full text |Cite
|
Sign up to set email alerts
|

The impact of occipital lobe cortical thickness on cognitive task performance: An investigation in Huntington's Disease

Abstract: The heterogeneous pattern of associations found in the present study suggests that occipital thickness negatively impacts cognition, but only in regions that are linked to relatively advanced visual processing (e.g., lateral occipital, lingual regions), rather than in basic visual processing regions such as the cuneus. Our results show, for the first time, the functional implications of occipital atrophy highlighted in recent studies in HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 54 publications
(81 reference statements)
9
62
2
Order By: Relevance
“…The difference with our findings might be explained by the fact that our cohort consisted of a heterogeneous, relatively young group of premanifest HD gene carriers with a median estimated time to disease onset of 16 years, based on the survival analysis of (Langbehn, Brinkman, Falush, Paulsen, & Hayden, 2004). (Johnson et al, 2015;Nopoulos et al, 2010;Tabrizi et al, 2009) Only six premanifest participants in our study were within a decade or nearer to disease onset, which might explain the fact that we found no differences between controls and premanifest HD. (Johnson et al, 2015;Nopoulos et al, 2010;Tabrizi et al, 2009) Only six premanifest participants in our study were within a decade or nearer to disease onset, which might explain the fact that we found no differences between controls and premanifest HD.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…The difference with our findings might be explained by the fact that our cohort consisted of a heterogeneous, relatively young group of premanifest HD gene carriers with a median estimated time to disease onset of 16 years, based on the survival analysis of (Langbehn, Brinkman, Falush, Paulsen, & Hayden, 2004). (Johnson et al, 2015;Nopoulos et al, 2010;Tabrizi et al, 2009) Only six premanifest participants in our study were within a decade or nearer to disease onset, which might explain the fact that we found no differences between controls and premanifest HD. (Johnson et al, 2015;Nopoulos et al, 2010;Tabrizi et al, 2009) Only six premanifest participants in our study were within a decade or nearer to disease onset, which might explain the fact that we found no differences between controls and premanifest HD.…”
Section: Discussioncontrasting
confidence: 95%
“…Our findings that cortical morphology of the primary visual cortex in early HD remained unaffected is in line with other studies that did not found atrophy of the primary visual cortex in both early and advanced disease stages (Johnson et al, 2015;Nana et al, 2014;Nopoulos et al, 2010). Still, our study is the first study that provides evidence of preserved basic visual processing function in early stages of HD using task-based fMRI that involved a black-and-white checkerboard stimulus.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We highlight here that we previously reported on a total score involving number correct collapsed across all degrees of rotation in a different set of analyses (Johnson et al, 2015).…”
Section: Mental Rotationmentioning
confidence: 94%